2013
DOI: 10.1021/nl400395c
|View full text |Cite
|
Sign up to set email alerts
|

Direct Observation of Hole Transfer from Semiconducting Polymer to Carbon Nanotubes

Abstract: Carbon nanotubes have been proven to play significant roles in polymer-based solar cells. However, there is intensive debate on whether carbon nanotube behaves as a donor or acceptor in the semiconducting polymer:carbon nanotube composite. In this paper, we report a direct observation via Kelvin probe force microscopy (KPFM) that single walled carbon nanotubes (SWNTs) behave as hole transporting channels in poly(3-hexylthiophene-2,5-diyl) (P3HT)/SWNT heterojunctions. By comparing the surface potential (SP) cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 27 publications
0
21
0
Order By: Relevance
“…37,[44][45][46][47][48][49] In some studies such capability of carbon nanotubes is believed to play a pivotal role for facilitating exciton dissociation and constituting charge carrier transport highways. This does not sound creditable if it was plasmonic metal nanostructures that were involved.…”
Section: Charge Transfer Mechanism In Hybridsmentioning
confidence: 99%
See 1 more Smart Citation
“…37,[44][45][46][47][48][49] In some studies such capability of carbon nanotubes is believed to play a pivotal role for facilitating exciton dissociation and constituting charge carrier transport highways. This does not sound creditable if it was plasmonic metal nanostructures that were involved.…”
Section: Charge Transfer Mechanism In Hybridsmentioning
confidence: 99%
“…This does not sound creditable if it was plasmonic metal nanostructures that were involved. For example, Lang and Li reported the direct observation of hole transfer from a semiconducting polymer to carbon nanotubes 44 and Nismy et al reported the photoluminescence quenching in composite films made of carbon nanotubes and poly(3-hexylthiophene): [6,6]-phenyl-C 61 -butyric acid methyl ester, arising from hole transfer into carbon nanotubes. Nonetheless, considering usually lower charge carrier density in semiconductor nanostructures, in principle a large intensity drop with charge transfer could be anticipated.…”
Section: Charge Transfer Mechanism In Hybridsmentioning
confidence: 99%
“…It was reported that introducing carbon nanotubes into active layer of OSCs improves the power conversion efficiency [63,64] and possesses high open-circuit voltage [65,66]. Photoinduced holes transported from active layer to SWCNTs was observed using KPFM when SWCNTs fabricated on poly(3-hexylthiophene) (P3HT) film as well as on P3HT and 6,6-phenyl-C61-butyric acid methyl ester (PCBM) blended film [10,67]. SWCNTs were carefully coated on top of P3HT in order to expose both P3HT and SWCNTs (Fig.…”
Section: Charge Transfermentioning
confidence: 99%
“…Because of quantum confinement and their unique geometries, nanowires exhibit superior performance in applications such as field-effect-transistors (FETs) (Fan et al 2004), chemical sensors (Ahn et al 2008;Zhang et al 2004), photovoltaic cells (Garnett and Yang 2010;Lan and Li 2013), and optical electronics (Gu et al 2008). Nanowires can be synthesized routinely through different techniques today (Gudiksen et al 2002;Jiang et al 2002;Unalan et al 2008).…”
Section: Introductionmentioning
confidence: 99%